1982
DOI: 10.1085/jgp.80.5.785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca2+, cyclic GMP, and cyclic AMP added to artificial solution perfusing lingual artery on frog gustatory nerve responses.

Abstract: The lingual artery of the bullfrog was perfused with artificial solution and the effects of Ca 21, Ca-channel blockers (MnC12 and verapamil), cGMP, and CAMP added to the perfusing solution of the gustatory nerve responses were examined. The responses to chemical stimuli of group 1 (CaC12, NaCl, distilled water, D-galactose, and L-threonine) applied to the tongue surface were greatly decreased by a decrease in Ca 21 concentration in the perfusing solution, suppressed by the Ca-channel blockers, enhanced by cGMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Our findings that all sugar fractions (TC1‐22‐4, TC1‐22‐5, and TC1‐25‐1) induced contractile responses in prostate preparations initially suggested that carbohydrates might be involved in contractility. Sugars such as galactose and mannose have been reported to increase intracellular Ca 2+ by inducing Ca 2+ influx in a number of cells by activating T‐type Ca 2+ channels 20, 21. However, we observed no physiological activity on the isolated rat prostate from administering glucose, sucrose, and fructose.…”
Section: Discussioncontrasting
confidence: 68%
“…Our findings that all sugar fractions (TC1‐22‐4, TC1‐22‐5, and TC1‐25‐1) induced contractile responses in prostate preparations initially suggested that carbohydrates might be involved in contractility. Sugars such as galactose and mannose have been reported to increase intracellular Ca 2+ by inducing Ca 2+ influx in a number of cells by activating T‐type Ca 2+ channels 20, 21. However, we observed no physiological activity on the isolated rat prostate from administering glucose, sucrose, and fructose.…”
Section: Discussioncontrasting
confidence: 68%
“…Our own studies of the process of bitter taste transduction suggest that it is mediated by a cell surface receptor, which upon binding the appropriate ligand stimulates the synthesis of an intracellular second messenger, result-ing in the release of calcium from internal stores (Akabas et al, 1988). An increasing amount of evidence is accumulating that intracellular second messengers are important in the transduction of various taste modalities (Nagahama, Kobatake & Kurihara, 1982;Hwang et al, 1989;Striem et at., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…refs. 32,35,40,41,68). However, the significance of cyclic nucleotide effects remained controversial.…”
Section: Discussionmentioning
confidence: 99%
“…refs. 11,40). The effect of membrane-permeant bitter substances on the cAMP-phosphodiesterase is also controversial (e.g.…”
Section: Discussionmentioning
confidence: 99%